Correct solvability of the difference Pade schemes for parabolic equations in Holder spaces - Ashyraliev, A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study Padé difference scheme for the approximate solution of the Cauchy problem for parabolic equations generated by the Padé fractions $R_{j,l}$, of exponential approximation. We establish an estimate of the coerciveness of the difference schemes for $j=l-2, l-1$, or even $j=l$ in a smaller space than $C_0^{α}(E)$.